Toulmin Model Based Argument Diagnosing: Constructing and Evaluating in The Argumention Essay in Indonesia Efl Text Book - Nasution, Habib Syukri (Lembaga Riset Mutiara Akbar, 2024)
This research aims to describe and explain Toulmin's argument patterns in the 2017 revised edition of the 2017 High School English textbook for class XI curriculum. This type of research is qualitative research using document analysis methods. The subject of this research is the 2017 revised edition of the 2013 curriculum 2013 high school English textbook. This book was written by Herman Benyamin. The object of this research is Toulmin's argument pattern. Analysis of the arguments in the discourse in the book is based on Toulmin's arguments whose components consist of Claim (C), Ground (G), Warrant (W), Backing (B), Qualifier (Q), and Rebuttal (R). After finding a pattern in each discourse, a conclusion is given. The results of this research show that this book contains patterns formed in discourse. From the results of Toulmin's argument analysis, in topic 1, patterns C (10%), RC (10%), GC (10), GQC (10%), GWC were found. (10%), GWBC (10%), GWQC (10%), GWRC (10%), GWBQC (10), GWBQRC (10%), Topic 2 is in C (14.3%), RC (0), GC (14.3%), GQC (14.3%), GWC (14.3%), GWBC (14.3%), GWQC (14.3%), GWRC (0%), GWBQC (14.3%), GWBQRC (0%). Discourse that does not have an argument is 20% and there are arguments that are not good according to Toulmin's argument. According to Toulmin, a good argument from this book is 85%, meaning that the presentation of this argument in the 2013 edition of the high school English textbook issued by the government can be said to be very good